Parenting in mothers with borderline personality disorder and impact on child outcomes. Issue 3 (23rd July 2015) - Petfield, Lara; Startup, Helen; Droscher, Hannah; Cartwright-Hatton, Sam
Abstract : Question: This systematic review explores two questions: what parenting difficulties are experienced by mothers with borderline personality disorder (BPD); and what impact do these have on her children? Study selection and analysis: Studies had to include mothers with a diagnosis of BPD, who was the primary caregiver to a child/children under 19 years. PsycINFO and MEDLINE were screened (update: July 2014), yielding 17 relevant studies. Findings: Mothers with BPD are often parenting in the context of significant additional risk factors, such as depression, substance use and low support. Interactions between mothers with BPD and their infants are at risk of low sensitivity and high intrusiveness, and mothers have difficulty in correctly identifying their emotional state. Levels of parenting stress are high, and self-reported competence and satisfaction are low. The family environment is often hostile and low in cohesion, and mothers with BPD show low levels of mind-mindedness but high levels of overprotection of older children. Outcomes for children are poor compared with both children of healthy mothers, and mothers with other disorders. Infants of mothers with BPD have poorer interactions with their mother (eg, less positive affect and vocalising, more dazed looks and looks away). Older children exhibit a range of cognitive–behavioural risk factors (eg, harm avoidance, dysfunctional attitudes and attributions), and have poorer relationships with their mothers. Unsurprisingly, given these findings, children of mothers with BPD have poorer mental health in a range of domains. Conclusions: This review highlights the elevated need for support in these mother–child dyads.